Single‐center analysis of organ offers and workload for liver and kidney allocation. Issue 11 (27th July 2022) - Reddy, Vikrant; da Graca, Briget; Martinez, Eric; Ruiz, Richard; Asrani, Sumeet K.; Testa, Giuliano; Wall, Anji
Abstract : The volume of abdominal organ offers received by the Baylor Simmons Transplant Institute has increased over time, resulting in a higher workload for our donor call team. To quantify the increase in organ offers, determine the characteristics of these offers, and estimate the impact on our transplant center workload, we collected center‐specific organ offer data from May 2019 to July 2021 using the UNOS Center Acceptance and Refusal Evaluation Report and performed a time study that collected the number of communications and time spent on communications for organ offers made during a typical week. The total offers per month increased by 140% (270/month to 648/month), while the number of transplanted organs remained stable. In addition, the percentage of offers for organs that were never transplanted increased from 54% to 75%. In a representative week‐long time study, surgeons made 505, center coordinators 590, and answering service coordinators 318 distinct communications, averaging 3, 4, and 2 communications/hour. Between November 2019 and July 2021, offer‐related workload increased by an estimated 97%. These results demonstrate a sizeable inefficiency in abdominal organ allocation associated with a nonrecoverable cost to our transplant center. Abstract : This single center study delineates changes in the quantity and type of liver and kidney organ offers over a two‐year period, finding substantial increases in organ offers and workload that were primarily driven by non‐transplanted organs. See Adler and Husain comment on page 2499 .